2003
DOI: 10.1179/096797803225009319
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of mechanically alloyed Ti–Al–B nanocomposite consolidated by spark plasma sintering

Abstract: Recently much research has focused on adding metals or ceramics to TiB 2 to improve its mechanical properties by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…During the ball milling process, the particles sizes of powders experience a typical evolution, namely dramatic increase at the early stage, gradual decrease after a certain time and achieving a stable level at last. This result agrees well with the conclusions in previous reports [8,9] . At the early stage, high energy colliding and squeezing of ball/ball and ball/wall result in a severe plastic deformation of the powders and the deformed particles are cold-welded to large lamellar composite particles, which are usually much coarser than the original powders.…”
Section: Morphology Evolution Of the Powderssupporting
confidence: 94%
“…During the ball milling process, the particles sizes of powders experience a typical evolution, namely dramatic increase at the early stage, gradual decrease after a certain time and achieving a stable level at last. This result agrees well with the conclusions in previous reports [8,9] . At the early stage, high energy colliding and squeezing of ball/ball and ball/wall result in a severe plastic deformation of the powders and the deformed particles are cold-welded to large lamellar composite particles, which are usually much coarser than the original powders.…”
Section: Morphology Evolution Of the Powderssupporting
confidence: 94%
“…Nayak et al [28] reported that MA of dilute Al-Fe alloys containing 2.5-10 at% Fe for 20 h resulted in the formation of α-Al, but heat treatment at high temperature (i.e., 500 • C) enabled α-Al to precipitate out Al 13 Fe 4 intermetallic. Lee et al major product of the Al-Fe reaction can be identified as Al 13 Fe 4 (also denoted as Al 3 Fe); however, formation of minor amounts of Al 5 Fe 2 was also seen. [29] TiB 2 has formed after 30 h of milling and thus several peaks of this phase appeared in the XRD pattern as shown in Figure 3.…”
Section: Effect Of Milling Time On Xrd Patternsmentioning
confidence: 94%
“…It has a high melting point (above 3000 • C), good creep resistance, good thermal conductivity, high electrical conductivity, excellent wear and corrosion resistance, and considerable chemical stability. [13][14][15][16] However, the formation of conventional TiB 2 is difficult and this is the major reason for its high cost and limited scope in engineering applications. [17] Composites reinforced by ceramic particles have been successfully fabricated by casting methods [18][19][20] and powder metallurgy (P/M) such as cryomilling, [21,22] ball milling, [23] and wet mixing process.…”
Section: Introductionmentioning
confidence: 99%
“…Composites obtained in Ti-Al systems and technologies of their fabrication are the subject of continuous intensive investigations due their practical applications. They are attractive materials for aerospace, machine and chemical applications [1][2][3][4][5] . They have high specific strength under tensile and compression conditions, good high temperature corrosion, oxidation and wear resistant properties and widely used in chemical technologies.…”
Section: Introductionmentioning
confidence: 99%